A Mutual Survival of Destructiveness and Its Creative Potential for Agency and Desire. Issue 1 (2nd January 2016) - Levine, Lauren
Abstract : In this paper, I explore ways in which a mutual survival of destructiveness became a source of agency, passion, and creative change for both analyst and patient. I describe how my patient, Jack pushed me to the brink, to the edge of my capacity as an analyst, and how each of us needed to free ourselves from old identifications and constraints in order to have the courage to swim together in dangerous, deadly waters. This deep mutual vulnerability helped us envision a sense of psychic future (Cooper, 2010; Loewald, 1960), allowing for catastrophic change (Bion, 1970/1984) and creative transformation.